Impact of Three Methods of Ischemic Preconditioning on Ischemia-Reperfusion Injury in a Pig Model of Liver Transplantation. Issue 4 (3rd April 2022) - Belon, Alessandro Rodrigo; Tannuri, Ana Cristina Aoun; de Albuquerque Rangel Moreira, Daniel; Figueiredo, Jose Luiz; da Silva, Alessandra Matheus; Serafini, Suellen; Guimarães, Raimundo Renato; Faria, Caroline Silverio; de Alexandre, Alcione Sanches; Gonçalves, Josiane Oliveira; Paes, Vitor Ribeiro; Tannuri, Uenis
Abstract: Background: Ischemic preconditioning (IPC), either direct (DIPC) or remote (RIPC), is a procedure aimed at reducing the harmful effects of ischemia-reperfusion (I/R) injury. Objectives: To assess the local and systemic effects of DIPC, RIPC, and both combined, in the pig liver transplant model. Materials and methods: Twenty-four pigs underwent orthotopic liver transplantation and were divided into 4 groups: control, direct donor preconditioning, indirect preconditioning at the recipient, and direct donor with indirect recipient preconditioning. The recorded parameters were: donor and recipient weight, graft-to-recipient weight ratio (GRWR), surgery time, warm and cold ischemia time, and intraoperative hemodynamic values. Blood samples were collected before native liver removal (BL) and at 0 h, 1 h, 3 h, 6 h, 12 h, 18 h, and 24 h post-reperfusion for the biochemical tests: aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), creatinine, BUN (blood urea nitrogen), lactate, total and direct bilirubin. Histopathological examination of liver, gut, kidney, and lung fragments were performed, as well as molecular analyses for expression of the apoptosis-related BAX (pro-apoptotic) and Bcl-XL (anti-apoptotic) genes, eNOS (endothelial nitric oxide synthase) gene, and IL-6 gene related to inflammatory ischemia-reperfusion injury, using real-time polymerase chain reaction (RT-PCR). Results: There were no differences between the groups regarding biochemical and histopathological parameters. We found a reduced ratio between the expression of the BAX gene and Bcl-XL in the livers of animals with IPC versus the control group. Conclusions: DIPC, RIPC or a combination of both, produce beneficial effects at the molecular level without biochemical or histological changes.